2017
DOI: 10.1002/cbdv.201700184
|View full text |Cite
|
Sign up to set email alerts
|

A New Anti‐Inflammatory Alkaloid from Roots of Heracleum dissectum

Abstract: Using various chromatographic methods, a new piperidinone alkaloid, (3S)-3-{4-[(1E)-3-hydroxyprop-1-en-1-yl]-2-methoxyphenoxy}piperidin-2-one (1), together with 10 known compounds, bergapten (2), xanthotoxol (3), isopimpinellin (4), isobergapten (5), heratomol-6-O-β-d-glucopyranoside (6), scopoletin (7), apterin (8), 3-methoxy-4-β-d-glucopyranosyloxypropiophenone, (praeroside; 9), tachioside (10) and coniferin (11), were isolated from roots of Heracleum dissectum Ledeb. Their structures were elucidated on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
(18 reference statements)
1
17
0
Order By: Relevance
“…The present study showed that xanthotoxol alleviated inflammation through suppressing the secretions of NO, IL-6, and TNF-α and expressions of iNOS and COX-2 in LPS-induced RAW 264.7 cells. These results were consistent with the previous study, which reported that xanthotoxol has an anti-inflammatory effect [ 30 ]. However, this earlier study only excludes the role of NO; the underlying molecular mechanisms remain to be explored.…”
Section: Discussionsupporting
confidence: 94%
“…The present study showed that xanthotoxol alleviated inflammation through suppressing the secretions of NO, IL-6, and TNF-α and expressions of iNOS and COX-2 in LPS-induced RAW 264.7 cells. These results were consistent with the previous study, which reported that xanthotoxol has an anti-inflammatory effect [ 30 ]. However, this earlier study only excludes the role of NO; the underlying molecular mechanisms remain to be explored.…”
Section: Discussionsupporting
confidence: 94%
“…In the study, bioactive compounds were identified in the extract, namely apiin, apigetrin, saponarin, rutin, diosmin, hesperidin, and xanthotoxol [7]. These compounds have been shown to possess anti-inflammatory and antioxidant activity [50][51][52][53]. Further studies should be conducted to confirm the potential antidiabetic effects of the compounds in vivo as well as their mechanisms of action.…”
Section: Effects On Diabetesmentioning
confidence: 99%
“…In the last few years, there has been an increased interest in naturally occurring coumarins due to their various biological and pharmacological properties and their low toxicity. It has been shown that they possess anticancer [ 25 ], antibacterial [ 26 ], antifungal [ 27 ], anti-inflammatory and antiviral [ 28 ], anticonvulsant [ 29 ], antihyperglycemic [ 30 ], triglyceride-lowering [ 31 ], antioxidant [ 32 ], bronchodilator [ 33 ], and vasodilator [ 34 ] effects. The molecular modeling of coumarins and various types of substitutions in their nuclei, represented by benzo-α-pyrone, may open new directions in the search and design of new, more potent compounds as effective adjuvants for the treatment of various diseases [ 35 ].…”
Section: Introductionmentioning
confidence: 99%